Faith, Islam and Ihsan in Forming Insan Kamil in the Perspective of Ibn 'Arabi (Thematic Interpretation Study): Iman, Islam dan Ihsan dalam Membentuk Insan Kamil Perspektif Ibnu ‘Arabi (Kajian Tafsir Tematik) - Muhamad, Ai Rohmatul Zakiah; Sari, Azzura Melan (Institut Agama Islam Negeri Kerinci, 2024)
Faith, Islam and ihsan are the three main pillars in the religious teachings brought by the Prophet Muhammad. They are often mentioned in the Qur'an, which is the source of Islamic teachings. There are many terms in the Quran related to faith, Islam, and ihsan. With faith, Islam and ihsan a person can reach the degree of insan kamil. This article will focus on the study of thematic interpretation that intends to collect verses of the Qur'an based on a particular theme, then connected with the figure of insan kamil in the perspective of Ibn 'Arabi. The method used in this study is a literature study by collecting data from various books of tafsir and focusing on thematic tafsir studies, and various kinds of literature that contain the content of insan kamil in Ibn 'Arabi's perspective, in order to obtain a conclusion. Islam, faith, and ihsan can shape a person to become insan kamil, more specifically in Ibn ''Arabi's perspective. The mention of Islam in the Qur'an occurs 73 times. Lafaz iman in the Qur'an is mentioned 814 times, while lafaz ihsan in the Qur'an is mentioned 108 times. Faith, Islam and ihsan are a unity in religion that cannot be separated from one another, in other words, the three are interconnected. To form the figure of Insan Kamil, humans must first have Islamic faith and ihsan in living their lives. This study shows the importance of having Islamic faith and ihsan in order to make him insan kamil, the ideal figure desired by Allah.